Šiaurinių širvintiškių i, ē ir i̯ā kamienų daiktavardžių raida - Markevičius, Aurimas (Baltistica, 2008)
DEVELOPMENT OF THE i, ē AND i̯ā STEM NOUNS IN THE NORTHERN ŠIRVINTIŠKIAI SUBDIALECT The present article is a joint analysis of three noun stems, as the majority of their endings have become syncretic due to phonetic and morphological development, and the above process resulted in good conditions for mixing of the said stems. Mostly the development of baritone stress i, ē and i̯ā stem nouns is discussed in the article, as unstressed endings have changed to a greater extent than stressed ones in the majority of Eastern Aukštaitian dialects. Quite a number of linguists attribute the majority of morphological changes to essentially phonetic changes. Numerous phonetic and accentual processes have taken place in different case endings of i, ē and i̯ā stem nouns of the Northern Širvintiškiai subdialect (in the localities of Kavarskas, Vidiškiai, Ukmergė and Pašilė). The main processes were Leskien’s law (having resulted in the shortening of as many as fifteen case endings), shortening of unstressed long vowels (as unstressed endings were devoid of long vowels), fronting of the vowels a and ā preceded by palatalised consonants (this resulted in conditions for the baritone stress I̯ā stem to develop into the ē stem, cf. nom. sg. *saujā > *saujē “handful” vs. *dulkē “dust”, gen. sg. *saujās > *saujēs vs. *dulkēs etc.), monophthongisation of circumflex and unstressed word‑ending diphthongs ‑ai, ‑ei and ‑ui (the dative case singular endings of all‑stem nouns have become syncretic, e.g. ká․rvi “for a cow”, í․lti “for a fang”, se̾․seri “for a sister”), etc. Following the aforementioned and other changes, a considerable part of case endings belonging to i, ē and I̯ā stem nouns have also become syncretic. Only the singular nominative case nouns with all the three stems have two different endings (e.g. í․ltis “fang”, sá․uje “handful”, dú․lke “dust”). All the remaining singular cases have identical endings. Syncretism is also found among some of the case endings in the plural. Conditions developed for i stem nouns to become members of the ē stem paradigm. Only a very small fraction of i stem baritone stress nouns have remained: í․ltis “fang”, nó·sis “nostril”, pí․ntis “axe head”, klέ̤·tis “granary”, pá․ltis “piece of back bacon” and sví․rtis “lever”. The stable ē stem was preserved well and furthermore enhanced with I̯ā and i stem words. Out of the morphological changes, the most important one is the elimination of system symmetry (substitution of bivocal endings with monovocal ones, e.g. *iltimus > iltims “for fangs”, *iltiji > iltiI̯ “in a fang” etc.). This tendency was typical of all the grammatical cases having bivocal endings except the plural inessive and illative, which have main long forms (e.g. dú․lkese “in dust” and dú․lkesnα “into dust”) in addition to short forms (dú․lkes “in dust, into dust”). The preserved forms with bivocal endings retain the inessive‑illative opposition. The dual number has nearly disappeared in all the stems. In the area of Northern Širvintiškiai, the emergence of the syncretic singular and dual accusative case due to phonetic development was particularly unfavourable for the retention of the dual number: the word í․lti may signify “one fang” (acc. sg.) and “two fangs” (acc. dual). After the disappearance of bivocal endings, unpopular consonant combinations like ‑mp, ‑sp developed in the adessive and allative cases, e.g. iltiesp “towards a fang”, ilčiump “towards fangs”. Besides this, they competed with prepositional constructions and were eventually substituted with such phrases entirely.